2018
DOI: 10.1159/000490855
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Tc22 and Th22 Cells in Myasthenia Gravis Patients and Their Significant Reduction after Thymectomy

Abstract: Objectives: Myasthenia gravis (MG) is an autoimmune disease accompanied by a thymic pathology and in most patients thymectomy (TE) is used as the therapeutic approach. Both B and T cells play an important role in MG pathogenesis. Methods: Twelve pre- and post-TE MG patients and 12 healthy controls (HCs) were enrolled. The mean percentages of Th22 and Tc22 cells were evaluated in MG patients (before and 6 months after TE) and HCs. Results: The mean percentage of Tc22 cells in pre-TE patients was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…It is thought that its efficacy is based on the removal of ectopic germinal centers and local pathogenic cells that drive the production of anti-AChR autoantibodies [ 20 ]. In our study, the signature populations rebounded in the blood after surgical removal of the inflammatory niche supporting the notion of pathological inflammatory leukocyte retention in the thymus during MG. Robat-Jazi and colleagues found significantly decreased IL-22 + Th cells in the blood of MG patients after thymectomy (compared to before thymectomy) [ 35 ], which is in accordance with our results of reduced IL-22 production by Th CD103 cells after removal of the thymus.…”
Section: Discussionsupporting
confidence: 92%
“…It is thought that its efficacy is based on the removal of ectopic germinal centers and local pathogenic cells that drive the production of anti-AChR autoantibodies [ 20 ]. In our study, the signature populations rebounded in the blood after surgical removal of the inflammatory niche supporting the notion of pathological inflammatory leukocyte retention in the thymus during MG. Robat-Jazi and colleagues found significantly decreased IL-22 + Th cells in the blood of MG patients after thymectomy (compared to before thymectomy) [ 35 ], which is in accordance with our results of reduced IL-22 production by Th CD103 cells after removal of the thymus.…”
Section: Discussionsupporting
confidence: 92%
“…They also showed a higher IL‐22 gene expression in patients with MG, which is consistent with a prior study 65 . Moreover, it has been shown that the frequency of Tc22 cells was elevated in MG patients compared to healthy controls, and this Tc22 frequency has been reduced significantly within 6 months of thymectomy 64 . The Th22/Tc22 ratio was significantly lower in MG patients than in the controls.…”
Section: Th22 In Autoimmune Disorderssupporting
confidence: 88%
“…The frequency of Th22 cells in patients treated with TE was not significantly different from that of the healthy controls. After TE surgery, the frequency of Th22 cells was significantly reduced ( 93 ). Studies have also shown that the levels of IL-17 mRNA in PBMC and IL-17 concentrations in serum increase while levels of IL-22 mRNA and serum IL-22 decrease in MG patients.…”
Section: Th22 Cells In Autoimmune Diseasesmentioning
confidence: 99%